2023
DOI: 10.1371/journal.pone.0281473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of personality traits on bus drivers’ prosocial and aggressive behaviours: The moderated mediating role of risk perception and gender

Abstract: Purpose The present study aimed to examine the effects of personality traits on bus drivers’ self-reported prosocial and aggressive driving behaviours as well as the mediating role of risk perception and the moderating role of gender in this relationship. Methods Three hundred and ten bus drivers who were 24–57 years old agreed to participate in this study. The measures utilized included personality scales, a risk perception scale and a prosocial and aggressive driving behaviour scale. Results A moderated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
0
0
1
Order By: Relevance
“…In addition, the authors found that the instruction to participants to use the reappraisal strategy rather than suppression was more effective. These results are in line with several studies that have highlighted the link between aggression and risky driving behaviour [47,[87][88][89][90][91], specifically in young drivers [92][93][94][95][96]. Indeed, adolescents and young adults up to 25 years are still in a cognitive development stage; hence, they are more likely to show strong impulsive reactions and physical arousal toward risk [35].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the authors found that the instruction to participants to use the reappraisal strategy rather than suppression was more effective. These results are in line with several studies that have highlighted the link between aggression and risky driving behaviour [47,[87][88][89][90][91], specifically in young drivers [92][93][94][95][96]. Indeed, adolescents and young adults up to 25 years are still in a cognitive development stage; hence, they are more likely to show strong impulsive reactions and physical arousal toward risk [35].…”
Section: Discussionsupporting
confidence: 90%
“…Recentemente, a literatura tem destacado as variáveis de personalidade como preditoras tanto da perceção de risco quanto do desempenho/comportamento de segurança, contribuindo para a compreensão dos comportamentos individuais e sociais (Santos, 2020). O crescente interesse na relação entre personalidade e desempenho/segurança no trabalho (Barrick & Mount, 1991) decorre da utilidade dos traços de personalidade como ferramentas preditivas e descritivas para o comportamento e desempenho específico de cada indivíduo (e.g., Liu & Yang, 2023;Wang et al, 2023). Num estudo centrado na perceção de risco, Sjöberg e af Wåhlberg (2002) incluíram traços de personalidade como preditores da perceção de risco.…”
Section: Introductionunclassified